Towards an embodied understanding of the sustainability of consumer choice—the case of fashion shopping - Solér, Cecilia (Frontiers in Sustainability, 2022)
This conceptual article describes how the concept of embodiment can contribute to research on sustainable consumption by highlighting how shopping as an embodied experience is shaped by the shopping marketplace. An embodied view recognizes that shopping reflects consumer dispositions, to purchase goods and services, that to a large extent are produced and sustained by socio-material marketplaces. Using the example of fashion shopping this article illuminates how such an embodied view of purchasing can enrich our understanding and competence in promoting shopping of sustainable products and, as in the case of fashion, endorse reduced shopping of novel garments. This article aims to enrich the structural strand of sustainable consumption research by describing how the sustainability of individual shopping can be understood as skills and dispositions acquired within, or in relation to, marketplaces activities and discourses. It suggests that current Western unsustainable fashion shopping practices, characterized by excessive consumption only will change if supply and communication practices in fashion marketplace change.